Nickel‐induced VEGF expression via regulation of Akt, ERK1/2, NFκB, and AMPK pathways in H460 cells - Wang, Jui‐Chin; Chen, Shih‐Yin; Wang, Meilin; Ko, Jiunn‐Liang; Wu, Chieh‐Lin; Chen, Ching‐Chung; Lin, Hui‐Wen; Chang, Yuan‐Yen (Environmental toxicology, 2019)
Prospective cohort studies have indicated that a highly nickel‐polluted environment may severely affect human health, resulting in such conditions as respiratory tract cancers. Such exposure can trigger vascular endothelial growth factor (VEGF) expression. However, the signal transduction pathways leading to VEGF induction by nickel compounds are not well understood. This study revealed the occurrence of VEGF induction in human non‐small‐cell lung cancer H460 cells exposed to NiCl2. Moreover, exposing H460 cells to NiCl2 activated extracellular signal‐regulated protein kinase (ERK), nuclear factor kappa B (NFκB), and protein kinase B (Akt) as well as downregulated AMP activated protein kinase (AMPK) expression. The mitogen‐activated protein kinase (MAPK) and ERK inhibitor significantly blocked NiCl2‐induced ERK activation and VEGF production. Pretreating H460 cells with a PI3K/Akt inhibitor substantially inhibited NiCl2‐induced VEGF expression and reduced Akt, ERK, and NFκB phosphorylation. Furthermore, 5‐aminoimidazole‐4‐carboxamide ribonucleoside‐induced AMPK activation improved VEGF expression in NiCl2‐treated H460 cells significantly. These results indicate that NiCl2 induces VEGF production through Akt, ERK, NFκB activation and AMPK suppression and mediates various types of pathophysiological angiogenesis.